Chapter Un'introduzione ai servizi eco-territoriali - Magnaghi, Alberto (Territori, 2020)
The text supports the introduction, alongside ecosystems services, of eco-territorial services, which unlike the former depend for their very existence on human care actions. To assess them (under a monetary or other perspective) it is necessary to distinguish between the use value and the existence value of each element of the territorial heritage: such a measure can drop to zero or rise to infinity, and is strongly dependent on the culture of the subjects who use it; this also requires the degree of self-determination of their communities to be included in the assessment.